On Display - Nitzan Zilberman (Footprint)
The focal point of this essay is the turn from the display of objects to the display of environments, a change that blurs the line between the body and the display, and arguably absorbs the subject into the object. This turn is enabled by the digital age, as well as ‘the experience economy’, and is manifested in the rise of immersive display systems. The Selfie Museum epitomizes this cultural shift. In the Selfie Museum, subject and object aren’t the sole dichotomies that are conflated; physical space combines with the virtual image; the still moment merges in the temporal experience; and two-dimensional projections are overlaid onto three-dimensional structures. As a result, architects become ‘experience designers’, virtual reality is a mode of design practice, and an ‘instagrammable’ moment is a project deliverable. In this essay I simultaneously acknowledge these changes and critique them. At the same time, I offer the combination of apparent oppositions as a potential new set of tools that can help rethink aspects of the architecture discipline and profession. By studying the Selfie Museum as both an architectural typology and a socio-political entity, I challenge the traditional museum as an institution, classic body image perceptions, and the common concept of a tourist destination.